The intention to use short videos for health information among Chinese adults: Based on the technology acceptance model - Junjiang Liu; Rui Huang; Jinluan Ren; Peifan Li; Pengfei Wang (Digital Health)
Objective The dissemination of health information plays a crucial role in health promotion. With the evolution of the Internet, short videos have become a significant medium for health information dissemination. This study aims to examine how short video features influence users’ intentions for health information and provide actionable recommendations for improving health communication strategies. Methods By integrating trust and perceived interactivity into the technology acceptance model, this study introduces a modified acceptance model for short videos. The model was evaluated through a survey conducted among 435 Chinese adults aged 18 and above, who had prior experience with short videos. The analysis was carried out using the partial least squares structural equation modeling technique for parameter estimation and model validation. Results The analysis revealed that the model accounts for 18.3% of the variance in perceived usefulness, 34.9% in attitudes towards the videos, and 26.4% in the intention to use them. Significant positive associations on usage intention were observed from trust (β = 0.184, P  < 0.001), perceived interactivity (β = 0.247, P  < 0.001), and attitude (β = 0.210, P  < 0.001). Perceived usefulness (β = 0.240, P  < 0.001), perceived ease of use (β = 0.213, P  < 0.001), trust (β = 0.173, P  < 0.001), and perceived interactivity (β = 0.152, P  = 0.001) were found to have significant positive associations with attitude. Conclusions Perceived usefulness, ease of use, trust, and perceived interactivity emerged as strong predictors of usage intention, with attitude serving as a mediating factor in the relationship between trust, perceived interactivity, and usage intention. These findings highlight the importance of creating authoritative, user-friendly, and engaging content of short videos to enhance health information dissemination effectiveness and credibility.